Perbandingan Nilai Persen Transmisi Eritema dan Pigmentasi Dengan Metode Maserasi dan Infusa Kopi Robusta (Coffea Canephora Pierre A. Frohner) Yang Berasal Dari Kabupaten Tana Toraja - Gina Yustika Rijar; Nurmala Sari; Ahmad Irsyad Aliah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research was conducted to determine the comparison of the present value of erythema transmission (%Te) for UV A and pigmentation (%Tp) for UV B using the cold method (maceration) and the hot method (infusion) of Robusta coffee using the spectrophotometric method. Sample extraction was carried out, then dilution was carried out on the ethanol extract and infusion at concentrations of 100 ppm, 120 ppm, 140 ppm, 160 ppm and 180 ppm, and obtained %Te, namely the extract concentration of 100 ppm including Fast tanning category, 120 ppm extra suntan category, concentration 140, 160, 180 ppm in the category of extra protection and % Tp all concentrations in the category of sunblock. the infusion has not reached the category of %Te and %Tp infusion of fast tanning category for concentrations of 100, 120, 140, 160 ppm and extra suntan at a concentration of 180 ppm.